Effects of High-Frequency Repetitive Transcranial Magnetic Stimulation on Upper Limb Dystonia in Patients With Wilson's Disease: A Randomized Controlled Trial - Hao, Wenjie; Wei, Taohua; Yang, Wenming; Yang, Yue; Cheng, Ting; Li, Xiang; Dong, Wei; Jiang, Hailin; Qian, Nannan; Wang, Han; Wang, Meixia (Frontiers in Neurology, 2021)
Background Upper limb myotonia is a frequent complication of Wilson’s disease (WD). It can lead to poor quality of life and disability. Currently, no effective treatment for it exists. Therefore, we carried out a clinical trial to determine whether high frequency repetitive transcranial magnetic stimulation (rTMS) on the primary motor cortex alleviates upper limb myotonia in WD patients. Methods This study was a single-center, double-blind, randomized clinical study, included 60 WD patients with upper limb myotonia from a research base of WD in Hefei,China.Participants were randomly divided into a treatment group (TG) and a control group (CG). The TG received seven 10 Hz rTMS sessions, while the CG received sham stimulation. Participants were assessed at baseline, after the seventh treatment session, and at two and four weeks after the seventh treatment session. The primary outcomes included patients’ objective muscle tension and stiffness as measured with the MyotonPRO device. The secondary results were scores on clinical scales assessing muscle spasm and motor symptoms, which included the Ashworth Scale (AS), Unified Wilson’s Disease Rating Scale (UWDRS), Burke Fahn Marsden Scale (BFM), and the Activities of Daily Living (ADL) scale. Results The analysis revealed that after 10 Hz rTMS, muscle tension (P < 0.01) and stiffness (P < 0.01) as measured by the MyotonPro device decreased significantly in the TG compared to the CG. Moreover, clinically relevant scale scores, including the AS (P < 0.01), UWDRS (P < 0.01), BFM (P < 0.01), and ADL (P < 0.01) were also significantly reduced. Conclusion High-frequency rTMS over the primary motor cortex may be an effective complementary and alternative therapy to alleviating upper limb myotonia in WD patients.